HALDUN TANER'İN ÖYKÜLERİNİN İZLEKSEL TAHLİLİİ - AYDIN, NESLİHAN (Fırat Üniveristesi, 2010)
Haldun Taner, Çağdaş Türk edebiyatının son dönemde yatişen en önemli öykü yazarlarından biridir. Karakter yaratmadaki özgünlüğü ve tema çeşitliliğiyle öykücülüğümüzde güçlü bir yere sahiptir. Onun güçlü ve özgün öykülerinin izleksel tahlilini yaptığımız bu çalışmamızı iki ana bölüm halinde düzenledik. Monografi nitelikli birinci bölümde Haldun Taner'in yaşamı, edebi kişiliği ve yapıtlarının değerlendirmesini yaptık. İkinci bölümde ise, Haldun Taner'in öykülerini izleksel açıdan tahlil ettik. Eserden yazara ulaşmayı hedefleyen bir değerlendirme tarzını esas aldığımız bu incelemede yazarın öykülerindeki anlam boyutunu bilimsel ve estetik yönden irdeledik.Anahtar Kelimeler: Haldun Taner, öykü, izlek, birey, anlam

Haldun Taner, who grew up in the last period of contemporary Turkish literature is one of the greatest story writer. With diversity of theme and originality in creating the character he has a strong place in Turkish?s storytelling.In this thesis, we tried to analyze his strong and original stories with regard to theme. We separated our work in two main parts. In the first part which has the quality of monograph, we made the assesment of Haldun Taner?s life, his literary, personality and his works of art.In the second part we analyzed stories with regard to theme. In this investigation in which we based on the method of an evaluation aiming at reaching to the writer through the work, we research his stories?s main dimension in accordance with science and art.Key words: Haldun Taner, story, theme, individual, sense
The theme analysis of Haldun Taner's stories
Keywords: Türk Dili ve Edebiyatı